Examining the internship challenges of students of the operating room and Anesthesia fields of Shahroud University of Medical Sciences - Paryab, Sahar; Mehryar, Hamidreza; Vahedi, Hamid; Dashtipour, Marjan; Garkaz, Omid (Shahroud Journal of Medical Sciences, 2025)
Background: Clinical training is an important and fundamental part of training in the operating room, the presence of any problems in clinical training will cause problems in the efficiency and effectiveness of this part of training. This study was conducted with the aim of investigating the internship challenges of students of the operating room and Anesthesia fields of Shahroud University of Medical Sciences.Methods: This descriptive-analytical study was conducted by census method on 113 students of Anesthesia and operating room of Shahroud University of Medical Sciences. that a series of entry and exit criteria were set at the beginning of the work, The data was collected with the help of the demographic information questionnaire and the Tolit et al. questionnaire, after which the data was entered into SPSS 18 and analyzed with the help of descriptive and analytical statistics.Results: In this study, the results showed that the average age of the participants was 22.47 ± 3.81 years. Most of the participants were female (63 individuals, 55.8%), from the operating room field (59 individuals, 52.2%), interested in their field of study (46 individuals, 40.7%), and satisfied with their field of study (84 individuals, 74.3%). A majority had an average economic status (81 individuals, 71.7%), were non-native students (71 individuals, 62.8%), and lived in dormitories (57 individuals, 50.4%). Regarding entry year, 33 students (29.2%) were admitted in 1401, and 62 participants (54.9%) were between 18 and 21 years old. Also, there was a significant relationship between gender (p = 0.001) and field of study (p = 0.001). satisfaction with field of study (0.001), economic status (0.001) and being native (0.001) with internship challenges. Among the subgroups of internship stressors, the most variable in both fields of Anesthesia was 18.88±4.71 and the operating room was 18.98±4.50 in the educational environment. And there was a significant relationship between the two groups in all subgroups. Also, the highest mean in the subgroups under investigation was the educational environment subgroup of 18.94±4.56.Conclusions: Since the educational environment plays an important role in solving educational challenges, special attention should be paid to these environments. Based on the findings of the current research, clinical education officials should reduce the challenging factors of clinical education by adopting and implementing effective decisions.